Activity of Oritavancin (LY333328), an Investigational Glycopeptide, Compared to That of Vancomycin against Multidrug-Resistant Streptococcus pneumoniae in an In Vitro Pharmacodynamic Model - Coyle, Elizabeth A. (American Society for Microbiology, 2001)
In the past 2 decades, multidrug-resistant Streptococcus pneumoniae has been encountered with increasing frequency around the world. This has led to the need for newer agents in the treatment of S. pneumoniae infections. Oritavancin (LY333328) is a new glycopeptide antibiotic with activity against gram-positive organisms; however, there is limited information on the pharmacodynamics of oritavancin with respect to the treatment of S. pneumoniae. We utilized an in vitro pharmacodynamic model to compare the activity of oritavancin to that of vancomycin against two penicillin-, macrolide-, and ciprofloxacin-resistant S. pneumoniae isolates (R919 and R921) over a 48-h period. Both oritavancin and vancomycin achieved 99.9% (3-log) kill, with oritavancin achieving the limit of detection (10(2) CFU/ml) within 1 h and vancomycin achieving this limit at 24 h for both isolates. Detection of resistance was not observed for oritavancin or vancomycin during the 48-h experiments. The key pharmacodynamic parameter for oritavancin has not been well defined. In our experiment, the ratios of the area under the curve from 0 to 24 h to the MIC of oritavancin, oritavancin plus albumin, and vancomycin for both isolates were greater than 944.5, and the ratios of the maximum concentration of drug in serum to the MIC ranged from 73.7 to 7188.5. T>MIC was 100% for oritavancin and vancomycin for both isolates. Oritavancin is a unique and potent antimicrobial that warrants further investigation against multidrug-resistant S. pneumoniae.